Perencanaan penanganan kawasan permukiman kumuh studi penentuan kawasan prioritas untuk peningkatan kualitas infrastruktur pada kawasan pemukiman kumuh di Kota Malang - Wijaya, Donny Wahyu (FIA UB, 2016)
Urban slum areas emerge due to lack of development in urban settlements and urban land constraints. This study aims to identify the characteristics of a slum area, determines the priority areas for improving the quality of infrastructures, and provides strategies to improving the quality of infrastructure slum areas in Malang Municipality. The results identify eleven classifications of slum areas and five priority areas for improving the quality of infrastructures. SWOT analysis suggests strategies to improve them which include conducting comprehensive planning improvement of the quality of infrastructures; improving coordination and synchronization of programs and activities; involving the community in the planning process; improving coordination and synergies with relevant institutions in the spatial use in the city area along in the border areas and riverbanks; increasing socialization as an effort to increase understanding and awareness for the public; and seeking opportunities for cooperation with the private sector in improving the quality of infrastructures.Â